2019
DOI: 10.1016/j.chempr.2019.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The “Framework Exchange”-Strategy-Based MOF Platform for Biodegradable Multimodal Therapy

Abstract: Despite all the efforts to develop an ideal technology for cancer treatment, vital parameters, such as reducing the adverse effects and improving treatment efficiency, still require significant improvement. For this purpose, the rational design of a smart stimuli-responsive and fully biodegradable delivery system is of great significance. By using ZIF-8 nanoparticles as a sacrificial template, black phosphorous quantum dots (BPQDs) and S-nitrosoglutathione (GSNO) were successfully encapsulated into HKUST-1@MIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…In the last few decades, metal–organic framework (MOF) nanomaterials have witnessed the development of nanotheranostic platforms. [ 26–30 ] For the high porosity and large surface area, many biocompatible MOF nanomaterials (e.g., MIL‐100, MIL‐101, ZIF‐8, etc.) have been used to carry small‐molecule theranostic agents.…”
Section: Methodsmentioning
confidence: 99%
“…In the last few decades, metal–organic framework (MOF) nanomaterials have witnessed the development of nanotheranostic platforms. [ 26–30 ] For the high porosity and large surface area, many biocompatible MOF nanomaterials (e.g., MIL‐100, MIL‐101, ZIF‐8, etc.) have been used to carry small‐molecule theranostic agents.…”
Section: Methodsmentioning
confidence: 99%
“…For the delivery and release of extraneous NO to the tumor, the selection of NO donor is particularly important. Up to now, many kinds of NO donors, including S-nitroso-N-acetylpenicillamine, [9] dinitrosyl iron complex, [10] sodium nitroprusside, [12,13] S-nitrosothiol, [7,14] S-nitrosoglutathione, [15] N-diazeniumdiolates, [16] l-Arginine (L-Arg), [8,17,18] and so on, [19][20][21] have been reported that can release NO under endogenous (e.g., glutathione, enzymes, pH, H 2 O 2 ) or exogenous stimuli (e.g., near-infrared light irradiation, ultrasound irradiation). Among them, as a semiessential amino acid to the body, L-Arg is a potential NO donor with excellent biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…A MIL-100(Fe) outer shell was added and nitrosogluthanione [ Appendix 1 . (entry 19)] was loaded into the pores to form HKUST-1@MIL-100(Fe) nMOFs (denoted G-BHM) [ 94 ]. In the presence of H 2 O 2 , copper ions released from the HKUST-1 internal framework can trigger the decomposition of nitrosogluthanione into nitric oxide, which, along with ROS generation of ferric ions, leads to cancer cell apoptosis.…”
Section: Targeted Therapymentioning
confidence: 99%